1989
DOI: 10.1128/jb.171.6.3095-3101.1989
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis flagellin gene (hag) is transcribed by the sigma 28 form of RNA polymerase

Abstract: The Bacillus subtilis gene hag, which codes for the flagellin structural protein, was identified by DNA sequence analysis in a collection of DNA fragments bearing in vitro promoters for the c28 form of RNA polymerase. The hag gene and adjacent, regions of the B. subtilis chromosome were restriction mapped, and the nucleotide sequence was determined. The hag gene was transcribed at all stages of growth from a single promoter that had sequences in the promoter recognition region characteristic of the consensus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(176 citation statements)
references
References 44 publications
(35 reference statements)
5
170
0
1
Order By: Relevance
“…Chloramphenicol (5 jig/ml), erythromycin (1 j,g/ml), and lincomycin (25 ,ug/ml) were added when appropriate. E. coli TG-2 was grown in LB, and ampicillin (30 transformants was found to contain pLM2, which contains a 1.9-kb PstI-EcoRI fragment as depicted in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chloramphenicol (5 jig/ml), erythromycin (1 j,g/ml), and lincomycin (25 ,ug/ml) were added when appropriate. E. coli TG-2 was grown in LB, and ampicillin (30 transformants was found to contain pLM2, which contains a 1.9-kb PstI-EcoRI fragment as depicted in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…This was accomplished by having primers synthesized which were complementary to sequences upstream of the gaps. In all cases the sequencing reactions were done with the reagents contained within the Sequenase kit (U.S. Biochemicals) and the DNA sequences were compiled and analyzed as described previously (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused our studies on three distinct cell types: motile, matrix-producing, and sporulating. These cell types can be distinguished by monitoring gene expression; hag encodes flagellin and is essential for motility (Mirel and Chamberlin 1989), the yqxM operon encodes the major protein component of the extracellular matrix Chu et al 2006), and sspB encodes a small acid-soluble protein found only in sporulating cells (see Fig. 1A; Setlow 1988).…”
Section: Biofilms Comprise Heterogeneous Populationsmentioning
confidence: 99%
“…In various Bacilli, sporulating cells are becoming hypermotile [3]. This upsurge in motility of B. subtilis has been related to the oD-dependent transcription of the flagellin gene [4]. It has been concluded from the DNA sequence analysis, that in B. subtilis as well as in E, coli and Salmonella typhimurium, chemotactic and flagellar genes are organized in a regulon containing promoters controlled by alternative sigma factors [5,.…”
Section: Introductionmentioning
confidence: 99%